PENGARUH IKLAN LAYANAN MASYARAKAT âSTOP PIRACYâ TERHADAP PENGETAHUAN KHALAYAK TENTANG PENCEGAHAN MEMBELI VCD/DVD BAJAKAN - nurfath, nurfath (WACANA, Jurnal Ilmiah Ilmu Komunikasi, 2012)
Stop piracy themed ads appear when the case is about piracy is spread throughout the world, including Indonesia. Piracy is considered harmful and dangerous industry VCD and DVD original makers and film industry. This ad is designed to raise public awareness in preventing trafficking and piracy industry develops VCD / DVD original.